Applying In Dubio Pro Natura in Environmental Crime Cases: Legal Perspectives in Indonesia - Ramli, Asmarani; Putra, Tegar Islami; Dewanti, Natasya Fitri; Kinasih, Salisa Widyaning; Arifin, Ridwan; Idris, Siti Hafsyah (The Indonesian Journal of International Clinical Legal Education, 2023)
This research aims to analyze the application of the "in dubio pro natura" principle in Indonesia. This principle translates as "in doubt, for nature" and emphasizes the importance of protecting nature and the environment in making legal decisions. This scientific research uses one of the parts of the grand method, namely Library Research which is based on literature or literature. The author uses several references as legal materials to analyze the object of writing. The results show that the application of the principle of "in dubio pro natura" is the foundation of the application of the concept of the precautionary principle that has entered the Indonesian legal order since the enactment of Law Number 32 of 2009, this principle is in line with the principles of environmental equity, bio diversity and polluter pays principle. In addition, this principle in Indonesia still faces challenges in its application. Several factors affecting the application of this principle in Indonesia include inconsistent government policies in environmental protection, lack of public understanding and awareness of the importance of nature conservation, and shortage of human and technical resources in environmental law enforcement.